Recurrent strokes in an occult case of recurrent Cutibacterium acnes prosthetic valve infective endocarditis: a case report. Issue 6 (29th May 2021) - Fry, Charles; Primus, Christopher P; Serafino-Wani, Robert; Woldman, Simon
Abstract: Background: Infective endocarditis (IE) is a known but uncommon cause of cardioembolic stroke and there are rare but recognized cases of IE without an inflammatory response. Cutibacterium acnes is an increasingly recognized source of invasive infections, including IE, but diagnosis is challenging due to its low virulence and fastidious nature. Case summary: A 47-year-old man presented with a multi-focal stroke suggestive of a cardioembolic source. Outpatient transoesophageal echocardiography (TOE) was concerning for vegetation or thrombus associated with his previous mitral valve repair. He remained clinically well, with no evidence of an inflammatory response and sterile blood cultures. Computed tomography–positron emission tomography (CT-PET) corroborated the TOE findings, however, given the atypical presentation, he was treated for valvular thrombus. Following discharge, he quickly re-presented with further embolic phenomena and underwent emergency mitral valve replacement. Intraoperative findings were consistent with prosthetic valve IE (PVE) and a 6-week course of antibiotics commenced. C. acnes was identified on molecular testing. Eighteen months later, he re-presented with further neurological symptoms. Early TOE and CT–PET were consistent with IE. Blood cultures grew C. acnes after prolonged incubation. Given the absence of surgical indications, he was managed medically, and the vegetation resolved without valvular dysfunction. He continues to be followed up in an outpatient setting. Discussion: In patients presenting with multi-territory stroke, IE should be considered despite sterile blood cultures and absent inflammatory response. C. acnes is an increasingly recognized cause of PVE in this context, often requiring surgical intervention. A high index of suspicion and collaboration with an Endocarditis Team is therefore essential to diagnose and treat.